2016
DOI: 10.1039/c5ra25933a
|View full text |Cite
|
Sign up to set email alerts
|

Aminal linked inorganic–organic hybrid nanoporous materials (HNMs) for CO2 capture and H2 storage applications

Abstract: Cyclophosphazene based nitrogen-rich aminal-linked inorganic–organic hybrid nanoporous materials were synthesized by a Schiff-base condensation reaction, which captures 18.9 wt% of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Therefore, MOF1 exhibits selectivea dsorption properties for CO 2 and can be ap otential candidate for gas separation applications. The higher value of CO 2 adsorption over other gases has been estimated ( Figure S8) by using Henry's [23] constanta nd the separation selectivities for CO 2 /H 2 , CO 2 /Ar,a nd CO 2 /N 2 are 93, 24, and 23, respectively.T he observed selectivity for CO 2 over other gases can be attributed to stronger interaction of acidic CO 2 with the basic ÀNH 2 functionalized pore of MOF1.…”
Section: Gas Adsorption Studiesmentioning
confidence: 99%
“…Therefore, MOF1 exhibits selectivea dsorption properties for CO 2 and can be ap otential candidate for gas separation applications. The higher value of CO 2 adsorption over other gases has been estimated ( Figure S8) by using Henry's [23] constanta nd the separation selectivities for CO 2 /H 2 , CO 2 /Ar,a nd CO 2 /N 2 are 93, 24, and 23, respectively.T he observed selectivity for CO 2 over other gases can be attributed to stronger interaction of acidic CO 2 with the basic ÀNH 2 functionalized pore of MOF1.…”
Section: Gas Adsorption Studiesmentioning
confidence: 99%
“…28 For example, the nitrogen with lone pair of electrons acts as Lewis base and could interact with Lewis acidic gases such as CO 2 . 5,[28][29][30][31][32] The presence of the ultramicroporosity could further be benecial for the H 2 storage application as H 2 is considered as an ideal fuel for future generation due to its much higher energy density than gasoline and non polluting nature. 5,[28][29][30][31][32] The presence of the ultramicroporosity could further be benecial for the H 2 storage application as H 2 is considered as an ideal fuel for future generation due to its much higher energy density than gasoline and non polluting nature.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphazene cyclomatrix polymers are highly cross‐linked and can be obtained by nucleophilic substitution reaction of chlorocyclophosphazenes with phenols or amines . Practical applications of these materials as efficient adsorbents for dyes, iodine or for CO 2 storage have been reported. Nevertheless, the use of phosphazene cyclomatrix materials for adsorption of metal ions has not been adequately addressed so far.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Phosphazene cyclomatrix polymers are highlyc ross-linked and can be obtained by nucleophilic substitution reactiono fc hlorocyclophosphazenes with phenols or amines. [43] Practical applications of these materials as efficient adsorbents for dyes, [44] iodine [45] or for CO 2 storage [46][47][48][49][50] have been reported. Nevertheless,t he use of phosphazene cyclomatrixm aterials for adsorption of metal ions has not been adequately addressed so far.O zcan et al have reported the synthesis of phosphazene microspheres by reacting hexachlorocycltriphosphazene( HCCP) or octachlorocycltetraphosphazene (OCCP) with diaminodiphenylmethane [51] and demonstrated their use for removal of Pb 2 + ions from water.L iet alh ave reported the application of ap orousp hosphazene-based crosslinked polymerf or effective extraction of uraniumi ons from water.T he hybrid polymer was prepared by reacting HCCP with phenylenediamine, hydroquinone and phlorogluci-nol.…”
Section: Introductionmentioning
confidence: 99%